Let "u=\\sin x" . We have "\\cos x dx= du" and "(z+z^3)du-(z+z^3)dy+(1-z^2)(y-u)dz=0" . That is "(z+z^3)(du-dy)+(1-z^2)(y-u)dz=0" .
Next, let "u-y=v" . Since "dv=du-dy" , we obtain "(z+z^3)dv+(1-z^2)(-v)dz=0."
Equality of the polynomials "1-z^2" and "Az^2+A+Bz^2+Cz=(A+B)z^2+Cz+A" gives us a system of equations
"=d\\ln |z|-\\frac{dz^2}{z^2+1}=d\\ln |z|-\\frac{d(z^2+1)}{z^2+1}="
"=d\\ln |z|-d\\ln |z^2+1|=d\\ln\\bigl|\\frac{z}{z^2+1}\\bigr|" .
Since "d\\ln |v| = d\\ln\\bigl|\\frac{z}{z^2+1}\\bigr|" , we have "\\ln |v| = \\ln\\bigl|\\frac{z}{z^2+1}\\bigr| + D" . Take the exponent of the equation: "|v| = e^D\\bigl|\\frac{z}{z^2+1}\\bigr|" . That is, "v = e^D\\frac{z}{z^2+1}" or "v = -e^D\\frac{z}{z^2+1}" . The case "v=0" also is a solution of the equation "(z+z^3)dv+(1-z^2)(-v)dz=0."
Union of the cases "v = e^D\\frac{z}{z^2+1}", "v = -e^D\\frac{z}{z^2+1}" and "v=0" is the case "v=E\\frac{z}{z^2+1}" .
Remembering that "v=u-y" and "u=\\sin x" , we have "\\sin x - y = E\\frac{z}{z^2+1}"
Answer: "\\sin x - y = E\\frac{z}{z^2+1}"
Comments
Leave a comment